Anatomical changes caused by Ralstonia solanacearum Smith and Pectobacterium carotovorum (Jones) in Solanum tuberosum L. stems - Hernández, Yonis; García, Marina; Mejías, Rafael (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Potato (Solanum tuberosum L.) is a crop notably affected by various pathogens, including bacterial, and it is important to study the histological changes that they produce to understand the symptoms associated with each disease. The objective of this research was to determine the anatomical changes that occur in potato stems due to the infection caused by Ralstonia solanacearum and Pectobacterium carotovorum. An assay was carried out with 45-day-old plants of the Kennebec variety, which were infiltrated in the basal part of the main stem with a suspension of 108 CFU.mL-1 of R. solanacearum and P. carotovorum, including a control treatment in which the plants were treated with sterile distilled water. Twelve days after inoculation, segments were taken from the second internode of the main stem and they were fixed in FAA (formaldehyde-acetic acid-ethanol 70 %) until processing to obtain cross sections of the stem. In the plants inoculated with R. solancaearum, invasion of the xylem vessels by the bacterium and formation of tyloses in some of them was observed. In the case of P. carotovorum, necrosis in the form of discontinuous bands in the epidermal cells, cortex, vascular cylinder, and pith was observed, as well as obstruction in xylem vessels by the bacteria and tylosis in some of them. The anatomical changes in the stem, induced by the two bacteria studied, are directly linked to the symptomatology of the disease that each of them causes in the potato crop.